Semiotic Analysis of Kekal Song by Nadin Amizah: Michael Rifaterre Study - Zalwa Aliya; Izzah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This analysis contains a semiotic analysis of Nadin Amizah's song "Kekal" using Riffaterre's study. The semiotic method used in this study is Riffaterre's semiotics. Riffaterre's theory explains that signs have elements of signifier and signified. The data collection techniques used are literature study, listening, and note-taking to identify parts of the lyrics that contain semiotic aspects. The data collection steps in this study are: (1) selecting song lyrics that contain semiotic aspects and using them as the data results, (2) describing the data according to the data obtained, and (3) explaining the data results with a theoretical perspective. The data analysis technique used is analysis with Riffaterre's theory, namely: 1) heuristic reading and hermeneutic reading (indirectness of expression), 2) matrix analysis, models, and variants, and 3) hypogram. The research results from the analysis of the song "Kekal" by Nadin Amizah are the journey of a couple's romantic relationship filled with affection and mutual acceptance of each other's weaknesses, hoping that their relationship will be eternal or eternal.